Changes in the communicative skills of young people as a result of a communication training - Maria Lucia Graziano Magalhães Torres; André Luiz Lopes Sampaio; Hugo Cesar Pinto Marques Caracas (CoDAS, 2023)
ABSTRACT Purpose To analyze the effect of communication training developed for adolescents on the youth’s communication skills. Methods Forty-one young people participated in the study and were divided into two groups. Group I received intervention - communication training for five weeks; Group II - were guided on the importance of voice for communication. Participants had their communication skills assessed before/after interventions through a self-administered questionnaire, answered by the participant and parents. Both groups had oral presentations recorded on video, which were analyzed by speech therapists through the evaluation of the communication profile, listing the aspects that should be observed as a point of strength/opportunity for improvement. Association between qualitative variables was assessed using Fischer’s exact test, Pearson’s chi-square test, McNemar’s test, and McNemar-Bowker’s test. To compare groups, paired t-test and t-test for independent samples, p level <0.05, were used. Results The analysis of questionnaires showed improvement in GI in two of the four skills assessed and no difference for GII. The video evaluations showed a significant difference between the groups in terms of eye contact and speech velocity. Conclusion This study points out that the communication training method applied to young people might improve communicative skills, providing some insights into their communication strengths and potential areas for development.